DESCRIPTION OF THE IMPACT OF ANXIETY IN ADOLESCENTS AGED 10-13 ON THE RISK OF PUBERTY DISORDERS AT SDN 4 CIKUNIR ELEMENTARY SCHOOL, TASIKMALAYA DISTRICT - Lisnawati, Lilis; Yunie, Chanty (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Early adolescence (aged 10-12 years) is the growth phase of puberty. During this time, the body undergoes significant adaptations, mainly guided by neuroendocrine factors that are crucial for reaching sexual maturity. Pubertal symptoms can often trigger anxiety, and become a stressor that complicates adjustment to physical and hormonal changes. This study aims to analyse the impact of anxiety in early adolescents on the risk of experiencing disorders during puberty. The observational research employed a descriptive analysis approach involving 40 adolescents aged 10 to 13. The total sampling method was used, with data collection instruments including height measuring tools, weight scales, questionnaires, and checklists. The results from anxiety measurement, using the Revised Children's Manifest Anxiety Scale (RCMAS), indicated that 95% of male participants and 90% of female participants reported experiencing anxiety related to puberty. 15% of adolescent girls over nine years old and twenty-five percent of boys under nine years old experience precocious or early puberty. Among respondents, 7 (63.6%) were male, and 4 (36.4%) were female adolescents with a thin BMI. Regarding symptoms of precocious puberty, 60% were suspected to have central precocious puberty, while 40% were suspected to have peripheral precocious puberty. In conclusion, adolescents' lack of confidence and embarrassment due to taboos. There is a need for health counsellors to increase adolescents' knowledge.